Calendula glycolic extract enhances wound healing of alginate hydrogel - Gisele de Oliveira Krubniki Possa; Solange Chopek; Airton Vicente Pereira; Adriana Yuriko Koga; Marcia Regina Paes de Oliveira; Michele Dietrich Moura Costa (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To assess the cytotoxicity and wound healing properties of an alginate hydrogel containing calendula glycolic extract. Methods: Cell viability in murine fibroblasts (3T3 cells) was evaluated using MTT and SRB assays. The wound healing effect was tested in an incisional wound model on 50 female Wistar rats, divided into two groups: rats treated with alginate hydrogel (n = 25), and rats treated with calendula-alginate hydrogel. Wound healing was assessed by measuring wound retraction rate and histological analysis of lesion tissues over a 28-day period. Histological analyses were performed on days 2, 7, 14, 21, and 28 post-surgery to examine inflammatory infiltrate, macrophage count, and angiogenesis. Picrosirius red staining was used to compare the relative abundance of collagen types I and III fibers. Results: Cytotoxicity tests on 3T3 cells revealed increased cell viability with the calendula-alginate hydrogel. The calendula-alginate hydrogel also demonstrated a significant improvement in wound closure, supported by histopathological analysis, showing reduced inflammation, increased macrophage activity, and enhanced collagen deposition. Conclusions: These findings evidenced the therapeutic potential of combining calendula extract and alginate for promoting enhanced wound healing.